Perbandingan Konsumsi Energi Algoritma AES (256 Bit) dan Twofish (256 Bit) Pada Ponsel Berbasis Android - Allo, Serli Liling; Subali, M (Universitas Gunadarma, 2014)
Running an encryption/decryption application on cell phone will be followed by the running CPU, memory, and energy stored in the battery. However, the baterry energy is limited. Therefore, it is important to observe how much energy consummed by encryption/decryption algorhytm to be one of determiners in algorhytm selecting. The study aims at comparing the energy consumption algorhytm of AES (256 bit) and Twofish (256 bit) on Android-based cell phone. To achieve that, the current, voltage, and time encryption/decryption. In the study, the current and voltage encryption/decryption are obtained from direct measurement, while time encryption/decryption is from algorithm benchmark on SSE (Secret Space Encryptor) application program. Energy consumption is obtained from the current, voltage, and time encryption/decryption multiplication. The result indicates that energy consumption algorythm of AES (256 bit) is bigger than Twofish (256 bit).Keywords: AES (256 bit), Encryption/Decryption Energy Consumption, Twofish (256 bit)